Effects of vedolizumab, adalimumab and infliximab on biliary inflammation in individuals with primary sclerosing cholangitis and inflammatory bowel disease. Issue 2 (28th May 2018) - Tse, C. S.; Loftus, E. V.; Raffals, L. E.; Gossard, A. A.; Lightner, A. L.
Summary: Background: Primary sclerosing cholangitis (PSC) is a chronic, progressive cholestatic biliary disease associated with inflammatory bowel disease (IBD) with no known cure. Aim: To evaluate the effect of biological therapies on PSC progression in IBD patients. Methods: We performed a retrospective cohort study of 88 cases (75 unique patients with 12 patients treated >1 biologics) of IBD (48 ulcerative colitis, 24 Crohn's disease and 3 indeterminate colitis) with concomitant PSC who received biological therapy (42 infliximab, 19 adalimumab, 27 vedolizumab) between June 2002 and October 2017. Hepatic biochemistries were compared using the paired t ‐test (patients served as their own controls) ≤3 months before and 6‐8 and 12‐14 months after biological initiation. Radiographic information of biliary stenosis and liver fibrosis were obtained via abdominal ultrasound, abdominal magnetic resonance imaging and magnetic resonance elastography. Results: Use of adalimumab was associated with a significant decrease in alkaline phosphatase (ALP) after 6‐8 months ( P = 0.03; mean change −70 U/L, standard deviation [SD] 88 U/L) compared to vedolizumab (mean change +50 U/L, SD 142 U/L) or infliximab (mean change +37 U/L, SD 183 U/L) but the change was not significant after 12‐14 months ( P = 0.24). No significant decreases were observed with AST, ALT, total or direct bilirubin, elastography score or radiographic imaging of biliary tree dilation/strictures with any biological therapy after 6‐8 or 12‐14 months. Conclusions: Current evidence suggests that biological therapies used for the treatment of IBD are not effective treatments for PSC. Further study is needed to elucidate any potential beneficial effect of adalimumab on PSC. Abstract : Linked Content This article is linked to Ma and Kotze and Tse et al papers. To view these articles visithttps://doi.org/10.1111/apt.14858 andhttps://doi.org/10.1111/apt.14907 .